Canadian review of studies in nationalism = Revue canadienne des études sur le nationalisme - University of Prince Edward Island. (University of Prince Edward Island, 1988)
Absorbed: Canadian review of studies in nationalism. Bibliography 1988, ISSN 0317-7912.